Wanted, A National Teacher Supply Policy for Education:The Right Way to Meet The "Highly Qualified Teacher" Challenge - Linda Darling-Hammond; Gary Sykes (Arizona State University, 2003)
Teacher quality is now the focus of unprecedented policy analysis. To achieve its goals, the No Child Left Behind Act (NCLB) requires a "highly qualified teacher" in all classrooms. The concern with teacher quality has been driven by a growing recognition, fueled by accumulating research evidence, of how critical teachers are to student learning. To acquire and retain high-quality teachers in our Nation's classrooms will require substantial policy change at many levels. There exists longstanding precedent and strong justification for Washington to create a major education manpower program. Qualified teachers are a critical national resource that requires federal investment and cross-state coordination as well as other state and local action. NCLB provides a standard for equitable access to teacher quality that is both reasonable and feasible. Achieving this goal will require a new vision of the teacher labor market and the framing of a national teacher supply policy. States and local districts have vital roles to play in ensuring a supply of highly qualified teachers; however, they must be supported by appropriate national programs. These programs should be modeled on U.S. medical manpower efforts, which have long supplied doctors to high- need communities and eased shortages in specific health fields. We argue that teacher supply policy should attract well-prepared teachers to districts that sorely need them while relieving shortages in fields like special education, math and the physical sciences. We study the mal-distribution of teachers and examine its causes. We describe examples of both states and local school districts that have fashioned successful strategies for strengthening their teaching forces. Unfortunately, highly successful state and local program to meet the demand for qualified teachers are the exception rather than the rule. They stand out amid widespread use of under-prepared teachers and untrained aides, mainly for disadvantaged children in schools that suffer from poor working conditions, inadequate pay and high teacher turnover. The federal government has a critical role to play in enhancing the supply of qualified teachers targeted to high-need fields and locations, improving retention of qualified teachers, especially in hard-to-staff schools, and in creating a national labor market by removing interstate barriers to mobility.